2018
DOI: 10.4172/1948-5956.1000543
|View full text |Cite
|
Sign up to set email alerts
|

Blocking PD1/PDL1 Interactions Together with MLN4924 Therapy is a Potential Strategy for Glioma Treatment

Abstract: Objective: MLN4924, a pharmacological inhibitor of cullin neddylation, resulted in glioma cell apoptosis, deregulation of the S-phase of DNA synthesis and thus, offers great potential for the treatment of brain tumours. However, targeting the neddylation pathway with an MLN4924 treatment stabilized the hypoxia-inducible factor 1A (HIF1A), which is one of the main transcriptional enhancers of the immune checkpoint molecule PDL1 (programmid death ligand-1) in cancer cells. The influence of immune checkpoint mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 44 publications
0
24
0
Order By: Relevance
“…48,49 However, single blockade of immune checkpoint molecules (such as PD1 and PD-L1) cannot effectively eliminate cancer cells. 42,50 A combination with cancer immunotherapy might enhance the anti-tumor effect. 42 The results also suggested that the combination therapy could reverse tumor-induced immunosuppression and enhance anti-tumor immunity, as evidenced by the increase in tumor-infiltrating effector CD4 + T cells and CD8 + T cells, decrease in Treg cells and MDSCs, and the longer survival time of the tumor-bearing mice.…”
Section: Discussionmentioning
confidence: 99%
“…48,49 However, single blockade of immune checkpoint molecules (such as PD1 and PD-L1) cannot effectively eliminate cancer cells. 42,50 A combination with cancer immunotherapy might enhance the anti-tumor effect. 42 The results also suggested that the combination therapy could reverse tumor-induced immunosuppression and enhance anti-tumor immunity, as evidenced by the increase in tumor-infiltrating effector CD4 + T cells and CD8 + T cells, decrease in Treg cells and MDSCs, and the longer survival time of the tumor-bearing mice.…”
Section: Discussionmentioning
confidence: 99%
“…Differential expression of 7 established immune checkpoint genes in the low and high-risk groups was analyzed. These are, T cell immunoglobulin domain and mucin domain 3 (TIM3), programmed cell death 1 (PD1), PD1 interacts with programmed death ligand 1 (PDL1), cytotoxic T lymphocyte antigen 4 (CTLA4), T cell immunoreceptor with Ig and ITIM domains (TIGIT), long non-coding RNA MIR 155 host gene (MIR155HG), and CD48 [20][21][22][23][24] . This analysis evaluated the correlation between risk score and expression of the checkpoint genes.…”
Section: Analysis Of Correlation Between Risk Score and Expression Ofmentioning
confidence: 99%
“…MLN4924, a small molecular inhibitor of NAE [17,18], has been developed as a first-in-class neddylation inhibitor. Intensive studies reported that MLN4924 induced the accumulation of tumor-suppressive CRLs substrates to suppress cancer cell growth and metastasis both in vitro and in vivo , owing to the inhibition of Cullin neddylation and CRLs activation [[19], [20], [21], [22], [23], [24], [25], [26]]. Due to its high efficiency and well-tolerated toxicity in preclinical trials, MLN4924 has advanced into clinical trials for human hematological malignancies and solid tumors [[27], [28], [29], [30]].…”
Section: Introductionmentioning
confidence: 99%